2002
DOI: 10.1128/jb.184.22.6146-6154.2002
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Characteristic D-D-E Motif in IS1Transposase

Abstract: IS1 is an insertion element first identified in Escherichia coli (for a review, see reference 28). IS1 is only 768 bp in length and has imperfect terminal inverted repeats (IR) of about 30 bp (19,30). IS1 transposes to a new site and generates a duplication of a target sequence of 9 bp (in most cases) or 8 bp (in some cases) (13,14,17,29). IS1 has two open reading frames (ORFs), insA and BЈ-insB, which are required for transposing itself (18,25,26). insB is in the Ϫ1 frame with respect to insA. The Ϫ1 frameshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 54 publications
3
37
0
1
Order By: Relevance
“…(iv) Transposase organization Alignment of InsAB' from different members of the family confirmed the presence of a C-terminal DDE catalytic domain (137) and also revealed potential N-terminal ZF and HTH motifs (135,138). Addition of 1,10-phenanthroline, which shows a high affinity for zinc, prevented binding to IS1 IR, as did mutations in either of the two motifs whereas mutation of the DDE motif confirmed its importance in catalysis but not in binding (135,138).…”
Section: (Iii) Mechanismmentioning
confidence: 94%
“…(iv) Transposase organization Alignment of InsAB' from different members of the family confirmed the presence of a C-terminal DDE catalytic domain (137) and also revealed potential N-terminal ZF and HTH motifs (135,138). Addition of 1,10-phenanthroline, which shows a high affinity for zinc, prevented binding to IS1 IR, as did mutations in either of the two motifs whereas mutation of the DDE motif confirmed its importance in catalysis but not in binding (135,138).…”
Section: (Iii) Mechanismmentioning
confidence: 94%
“…Transphylum and even transdomain distribution of members of an IS family has been reported. Cassier-Chauvat et al identified an IS element found in the cyanobacterium Synechocystis which had a significant homolog in alphaproteobacteria (2), while the Shigella dysenteriae IS1 transposase exhibits amino acid identity of up to 48% with IS-encoded transposases in archaea (20). In contrast, copies of IS elements in closely related species often approach identity, reflecting very recent dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 3). Only the IS1 element (aec-38 to aec-40) seems to be intact and to possess its left and right terminal inverted repeats (47). All the other elements are disrupted either by frameshift or by integration of another IS element.…”
Section: Vol 188 2006mentioning
confidence: 99%